ART IN THE RUMAGHES UMBANUA OF LAIKIT VILLAGE: NEGOTIATING CHRIST TRANSFORMING CULTURE AND COLLABORATIVE PLURALISM - Jekson Berdame; Alrik Lapian; Febri Kurnia Manoppo; Tri Oktavia Hartati Silaban (Balai Penelitian dan Pengembangan Agama Makassar, 2026)
This study examines the cultural transformation of Rumaghes Umbanua in Laikit Village, North Minahasa,as a contemporary reconfiguration of the traditional Dumia Umbanua ritual into a public celebration ofgratitude shaped by interreligious participation and artistic performance. While previous studies haveexplored Minahasan thanksgiving traditions from pastoral, culinary, and ritual perspectives, limitedattention has been given to the role of art as a theological and social medium in pluralistic contexts. Thisresearch addresses that gap by analyzing how artistic expressions function as agents of contextual theologyand collaborative pluralism. Using a qualitative descriptive–interpretive approach, data were collectedthrough participatory observation, in-depth interviews with traditional leaders, religious leaders, artists,and community members, as well as document analysis of cultural and historical archives. The findingsindicate that artistic practices including Kabasaran dance, bamboo and kolintang music, interfaith choirperformances, and traditional attire serve not merely as aesthetic components but as performative spacesin which theological meanings, cultural identities, and interreligious relations are actively negotiated.Through the lens of Richard Niebuhr’s Christ Transforming Culture, the study suggests that RumaghesUmbanua represents a dynamic model of contextual theology in which Christian values transform culturalsymbols without entirely erasing their historical significance. At the same time, the findings highlight theambivalent nature of collaborative pluralism, in which inclusion is shaped by implicit power relations andnegotiated boundaries of representation. This study contributes to the discourse on contextual theology bypositioning art as an active theological mediator and a public instrument for social cohesion, identity reconstruction, and intercultural dialogue in multireligious societies